AKT2 regulates development and metabolic homeostasis via AMPK-depedent pathway in skeletal muscle. Issue 17 (16th September 2020) - Chen, Miao; Ji, Caoyu; Yang, Qingchen; Gao, Shuya; Peng, Yue; Li, Zhe; Gao, Xingyu; Li, Yaoting; Jiang, Nan; Zhang, Yubin; Bian, Xiaohong; Chen, Caiping; et al.
Abstract: Skeletal muscle is responsible for the majority of glucose disposal in the body. Insulin resistance in the skeletal muscle accounts for 85–90% of the impairment of total glucose disposal in patients with type 2 diabetes (T2D). However, the mechanism remains controversial. The present study aims to investigate whether AKT2 deficiency causes deficits in skeletal muscle development and metabolism, we analyzed the expression of molecules related to skeletal muscle development, glucose uptake and metabolism in mice of 3- and 8-months old. We found that AMP-activated protein kinase (AMPK) phosphorylation and myocyte enhancer factor 2 (MEF2) A (MEF2A) expression were down-regulated in AKT2 knockout (KO) mice, which can be inverted by AMPK activation. We also observed reduced mitochondrial DNA (mtDNA) abundance and reduced expression of genes involved in mitochondrial biogenesis in the skeletal muscle of AKT2 KO mice, which was prevented by AMPK activation. Moreover, AKT2 KO mice exhibited impaired AMPK signaling in response to insulin stimulation compared with WT mice. Our study establishes a new and important function of AKT2 in regulating skeletal muscle development and glucose metabolism via AMPK-dependent signaling.